Mechatronics, robotics and control special topic volume with invited peer reviewed papers only - Kot, Andrzej (Applied mechanics and materials ;, 2015)
The scope of the studies in this volume relate to issues ranging from theoretical considerations, ending with the application tests. The application uses are connected with biomedical engineering, vision systems application, and research on control algorithms. A wide field of research includes also work associated with the use of smart materials including, i.e. Shape Memory Alloys (SMA), piezoelectric or magnetorheological fluids.